STRUCTURAL CHANGES OF POMALAA LATERITIC ORE DUE TO COAL-BASED MAGNETIZING ROASTING - PRAMUSANTO PRAMUSANTO; NURYADI SALEH; SYONI SUPRIYANTO (Indonesian Mining Journal, 2011)
Overburden of Indonesia’s laterite ore at Pomalaa is considered as an iron cap. It performs low iron grade (41.88%) and high silica and aluminum oxide contents (18.47% and 9.46%, respectively). Around 54.74% of size distribution belong to -325 mesh fraction. Limonite iron mineral dominates in the ore in the range of 80-90% with water content of about 40%. Proven deposits of laterite iron ore are about  222 million tons. As a significant resources iron ore to be used as raw material for iron and steel industries, the iron content must be upgraded to meet the requirement of iron making industry. Magnetizing roasting technique can be conducted to change the paramagnetic iron mineral (such as hema- tite, goethite, limonite or siderite) into magnetite one that has high magnetic intensity. Therefore, the changed iron mineral can be concentrated using low-intensity, magnetic separator. Coal, mixed in ore composite may also enhance the development of coal-based magnetizing roasting processes in order to reach the desired temperature. Recently, reduced iron products from many different processes have been used as the main feed mixed with steel scrap. On the other hand, iron ore resources is getting dominated by low grade lateritic iron ore with specific content of water crystal. The abundant deposits of low grade lateritic iron ore and low rank coal in Indonesia can be used as suitable resources for raw materials in the iron and steel- making industry. Iron structural changes during magnetizing roasting process using coal as reductant agent was observed. The result showed that the non-magnetic limonite ore has been changed in to metallic iron and the iron recovery in the magnetic product depended on the coal ratio in the pellet composite. The magnetic product can be used for the development of lateritic iron ore as one of the alternatives to metallized iron feed for iron making industry.